2011
DOI: 10.3354/meps09399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating age in Octopus vulgaris: estimation, validation and seasonal differences

Abstract: Several internal structures have been used to estimate age in the cephalopod Octopus vulgaris, but with limited accuracy. We estimated age by investigating growth increments (rings) in the upper beaks of octopus collected between 2003 and 2010 in the Bay of Naples, Italy (Mediterranean Sea). To validate the daily periodicity of ring deposition, 'thermal shock marking' was for the first time applied to live octopuses fished between 2009 and 2010; this method produced a mark on the beak corresponding to the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 39 publications
3
41
0
Order By: Relevance
“…S. oualaniensis collected from warm water have the widest increments compared to I. argentinus and O. bartramii that were obtained from cold waters and had thinner increments. In addition, D. gigas from warm waters (Ecuador) have wider increments than those from cold waters (Chile) ( Table 2), as found in beaks of O. vulgaris LWS (Canali et al 2011). Such a pattern is also congruent with the findings in statolith (Villanueva 2000) and in cuttlebone (Chung and Wang 2013).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…S. oualaniensis collected from warm water have the widest increments compared to I. argentinus and O. bartramii that were obtained from cold waters and had thinner increments. In addition, D. gigas from warm waters (Ecuador) have wider increments than those from cold waters (Chile) ( Table 2), as found in beaks of O. vulgaris LWS (Canali et al 2011). Such a pattern is also congruent with the findings in statolith (Villanueva 2000) and in cuttlebone (Chung and Wang 2013).…”
Section: Discussionsupporting
confidence: 83%
“…Validation of the daily deposition of growth increments in beaks is widely studied in octopod O. vulgaris (Oosthuizen 2003;Canali et al 2011;Perales-Raya et al 2014a, b) and O. maya (Rodríguez-Domínguez et al 2013;Bárce-nas et al 2014). Unfortunately, unlike octopods and sepioids, squid are difficult to rear in the laboratory (Iglesias et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cannot be established as a general tendency in octopods on the basis of previous studies. Neither Hernandez-Lopez et al (2001) nor Canali et al (2011) found significant differences in lifespan between sexes in O. vulgaris. Conversely, Leporati et al (2008) found significant differences in age by reading O. pallidus stylets, although males were significantly longer-lived than females.…”
Section: Discussionmentioning
confidence: 85%
“…Particularly in octopods, beaks have provided some positive results in reading growth increments of Octopus vulgaris paralarvae (HernandezLopez et al 2001) and adults (Canali et al 2011, PeralesRaya et al 2010. Stylet Increment Analysis has been applied and daily growth increment deposition has been validated in Octopus vulgaris (Hermosilla et al 2010), Octopus pallidus (Doubleday et al 2006), Octopus maya (Rodríguez-Domínguez et al 2013) and Octopus (cf) tetricus (Leporati and Hart 2014).…”
Section: Introductionmentioning
confidence: 99%